Asymmetric total synthesis of (−)-conduramine A-1 via a chiral syn, anti-oxazine. Issue 17 (1st October 2016) - Myeong, In-Soo; Kim, Jin-Seok; Lee, Yong-Taek; Kang, Jong-Cheol; Park, Seok-Hwi; Jung, Changyoung; Ham, Won-Hun
Graphical abstract: Abstract: The total synthesis of (−)-conduramine A-1 was achieved by using a diastereomerically enriched syn, anti -oxazine intermediate. The key steps in this strategy were the stereoselective extension of the chirality of syn, anti -oxazine, a Wittig reaction, and a ring-closing metathesis reaction. Abstract : ( S )-1-((4 R, 5 S, 6 R )-5-(( tert -Butyldimethylsilyl)oxy)-4-((( tert -butyldimethylsilyl)oxy)methyl)-2-phenyl-5, 6-dihydro-4 H -1, 3-oxazin-6-yl)prop-2-en-1-ol: C26 H45 NO4 Si2 [ α ]D 25 = +16.1 ( c 0.5, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: ( S )-1-(4 R, 5 S, 6 R ) Abstract : ( R )-1-((4 R, 5 S, 6 R )-5-(( tert -Butyldimethylsilyl)oxy)-4-((( tert -butyldimethylsilyl)oxy)methyl)-2-phenyl-5, 6-dihydro-4 H -1, 3-oxazin-6-yl)prop-2-en-1-ol: C26 H45 NO4 Si2 [ α ]D 25 = +29.1 ( c 0.23, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: ( R )-1-(4 R, 5 S, 6 R ) Abstract : ( S )-1-((4 R, 5 S, 6 R )-5-(( tert -Butyldimethylsilyl)oxy)-4-((( tert -butyldimethylsilyl)oxy)methyl)-2-phenyl-5, 6-dihydro-4 H -1, 3-oxazin-6-yl)allyl acetate: C28 H47 NO5 Si2 [ α ]D 25 = +35.4 ( c 0.6, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: ( S )-1-((4 R, 5 S, 6 R ) Abstract : (3 S, 4 R, 5 S, 6 R )-3-Acetoxy-6-(((benzyloxy)carbonyl)amino)-5, 7-bis(( tert -butyldimethylsilyl)oxy)hept-1-en-4-yl benzoate: C36 H55 NO8 Si2 [ α ]D 25 = −2.6 ( c 0.6, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: (3 S, 4 R, 5 S, 6 R ) Abstract : (3 S, 4 R, 5 S, 6 R )-3-Acetoxy-6-(((benzyloxy)carbonyl)amino)-5-(( tert -butyldimethylsilyl)oxy)-7-hydroxyhept-1-en-4-yl benzoate: C30 H41 NO8 Si [ α ]D 25 = −100.0 ( c 0.3, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: (3 S, 4 R, 5 S, 6 R ) Abstract : (3 S, 4 R, 5 S, 6 R, E )-3-Acetoxy-6-(((benzyloxy)carbonyl)amino)-5-(( tert -butyldimethylsilyl)oxy)-8-phenylocta-1, 7-dien-4-yl: C37 H45 NO7 Si [ α ]D 25 = −15.1 ( c 0.6, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: (3 S, 4 R, 5 S, 6 R ) Abstract : (3 S, 4 R, 5 S, 6 R, Z )-3-Acetoxy-6-(((benzyloxy)carbonyl)amino)-5-(( tert -butyldimethylsilyl)oxy)-8-phenylocta-1, 7-dien-4-yl benzoate: C37 H45 NO7 Si [ α ]D 25 = +67.1 ( c 0.8, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: (3 S, 4 R, 5 S, 6 R ) Abstract : (1 R, 2 S, 5 R, 6 R )-2-Acetoxy-5-(((benzyloxy)carbonyl)amino)-6-(( tert -butyldimethylsilyl)oxy)cyclohex-3-en-1-yl benzoate: C29 H37 NO7 Si [ α ]D 25 = +100.0 ( c 0.6, CHCl3 ) Source of chirality: Fromd -serine and asymmetric synthesis Absolute configuration: (1 R, 2 S, 5 R, 6 R ) Abstract : (1 R, 2 R, 3 S, 6 R )-6-Aminocyclohex-4-ene-1, 2, 3-triol: C6 H11 NO3 [ α ]D 25 = −18.8 ( c 0.86, MeOH) Source of chirality : Fromd -serine and asymmetric synthesis Absolute configuration : (1 R, 2 S, 5 R, 6 R )